Effect of different doses of Ipil-Ipil (Leucaena leucocephala) (LAM.) de wit. tree green leaf biomass on rice yield and soil chemical properties (Research in Agriculture Livestock and Fisheries, 2015)
A field experiment was conducted to find out the effect of different doses of ipil-ipil (Leucaena leucocephala ) (Lam.) de Wit. tree green leaf biomass on rice yield and soil chemical properties. Four different treatments such as T0: Recommended fertilizer dose (Urea 195 kg/ha, TSP 50 kg/ha, MOP 142 kg/ha, Gypsum 75 kg/ha and Zinc Sulphate 4 kg/ha), T1: 5 t/ha, T2: 7.5 t/ha, and T3: 10 t/ha ipil-ipil tree green leaf was used in this study in a Randomized complete block design with three replications. The results showed that the treatment T3 was performed better than recommended fertilizer dose in case all yield contributing characters of rice except grain yield. The highest (5.29 t/ha) rice grain yield was obtained in recommended fertilizer dose followed by 10 t/ha, 7.5 t/ha and 5 t/ha ipil-ipil tree green leaf biomass amendment having 4.80, 3.16 and 2.36 t/ha respectively. The highest grain yield that was obtained from recommended fertilizer dose was 10.21% higher compared to the highest dose (10 t/ha) of ipil-ipil tree green leaf biomass. It was mentioned that among the different doses of ipil-ipil tree green leaf biomass 10 t/ha performed the best over others. The ipil-ipil tree green leaf biomass was also significantly influenced on some essential nutrient status which is very important for rice production. The highest amount of total N, available P, exchangeable K and available S were found in the treatment T3 and the lowest in the treatment T1. Therefore, it can be concluded that the ipil-ipil tree leaf has beneficial effects and could be combined with inorganic fertilizer for sustainable crop yield and maintaining soil fertility.Res. Agric., Livest. Fish.2(3): 385-394, December 2015